RELASl SAINS DAN AGAMA STUDI PEMIKIRAN IAN G BARBOUR - Damanhuri Damanhuri (Refleksi: Jurnal Filsafat dan Pemikiran Keislaman, 2015)
The relation between science and religion in the recent years is still interesting to study. The long history ofboth sides had created complex relation, harmony and disharmony. Nevertheless, the issue concerning relation between science and religion is not always created by conflict and tension. Many individual tries to connect them and the other supposes that there is no connection between them; both are different entities, having separate territory as a formal-material object (ontology), research method (epistemology), and their role (axiology). This writing tries to elaborate methodologically a scientist thought, Ian G Babour, which is brilliantly propose a relation pattern that can explicate the relation between science and religion, i.e. in form of conflict, independent, dialogue, or integration. From this fourth relation, Ian G Babour takes his place in position of dialogue and integration.